THE INITIATING ACTS USED BY THE HOST OF TALK INDONESIA IN POLITICAL AND CULTURAL ISSUES - Eka J. Saimima; Henny P.S. Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
The writers observed the initiating acts used by the host of Talk Indonesia in political issues and cultural issues and the comparison of initiating acts between those two issues. The data was taken from several episodes of the Talk Indonesia that have topics on political and cultural issues.  In the findings, the writers found that the highest percentage of initiating acts types in political issues is Inform (37%), and the lowest percentage is Action Request (1%), whereas, the highest percentage of initiating acts types in cultural issues is Inform (39%) and the lowest percentages are Polarity Questions (1%) and Action Requests (1%). The writer also found that in general, the percentage of Statement in the political issues (54%) is lower than those in the cultural issues (73%) while the percentage of Questions in the political issues (41%) is higher than those in the cultural issues (26%). The conclusion drew that different issues trigger different initiating acts